Initial development of the Coach Identity Prominence Scale: a role identity model perspective - Pope, J Paige; Hall, Craig R (Journal of sport & exercise psychology, 2014)
The focus of this multiphase research was to generate and test the psychometric parameters of the Coach Identity Prominence Scale (CIPS). First, a pilot study was conducted with context (n = 10) and construct (n = 6) specialists, who evaluated the technical quality and content validity of 20 items developed from semistructured interviews. Thirteen items were selected for Study 1, which tested the factorial validity and reliability scores of coaches' (n = 343) responses to the CIPS items. An eight-item structure, consisting of two factors (centrality and evaluative emotions) was selected as the final CIPS measure, which was examined with a final sample of coaches (n = 454) in Study 2 to evaluate the factorial validity, group invariance, concurrent validity, and nomological validity of respondents' scores to the CIPS. Initial evidence for the various types of validity and reliability tested across the studies was provided.